SOSIALISASI PENCEGAHAN KEKERASAN SEKSUAL, INTOLERANSI, DAN PERUNDUNGAN DI SDN 1 DEMANGAN NGANJUK GUNA MENINGKATKAN KEWASPADAAN SISWA - Putri, Erlina Amelia; Antono, Mixghan Norman; Kayati, Afiyah Nur; Puspitasari, Aditya Dyah; Faisal, Faisal (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2025)
Education is a major milestone for the nation's progress. Education has a role in shaping students' character in various sectors, including economic, social, cultural, technological and morality. Education will continue to develop according to the times, because advanced education will create a developed country too. Therefore, education, which is a second home for children, is expected to be a safe and comfortable place. In fact, the world of Indonesian education still has unresolved problems related to sexual violence, intolerance and bullying committed by students, teaching staff and the community outside the scope of education. If this problem is not handled properly, it will have a psychological and physical impact on the child. Therefore, it is necessary to hold community service to increase students' understanding of preventing sexual violence, intolerance and bullying behavior carried out at SDN 1 Demangan. Community Service activities use socialization and counseling methods by the service team. The results obtained from this service activity were an increase in students' understanding of the importance of preventing sexual violence, intolerance and bullying behavior, apart from that, students' awareness increased by almost 60% after receiving material provided by the service team.